2020
DOI: 10.1016/j.jpainsymman.2020.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Grief During the COVID-19 Pandemic: Considerations for Palliative Care Providers

Abstract: The COVID-19 pandemic is anticipated to continue spreading widely across the globe throughout 2020. To mitigate the devastating impact of COVID-19, social distancing and visitor restrictions in health care facilities have been widely implemented. Such policies and practices, along with the direct impact of the spread of COVID-19, complicate issues of grief that are relevant to medical providers. We describe the relationship of the COVID-19 pandemic to anticipatory grief, disenfranchised grief, and complicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
526
1
108

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 539 publications
(687 citation statements)
references
References 23 publications
14
526
1
108
Order By: Relevance
“…This has raised the sense of shock, and pain among individuals in the society and they were scared of dying in such circumstances. Similar evidence was reported by Wallace et al, 2020,families that were unable to grieve in accordance with traditional funeral practices or being unable to attend a loved one's burial undergo feeling of grief and sorrow [14] Our study found that the pandemic has caused signi cant nancial disruption among the community members. It was identi ed that many families were struggling hard in present time due to nancial insecurities including unemployment, and salary deduction.…”
Section: Discussionsupporting
confidence: 90%
“…This has raised the sense of shock, and pain among individuals in the society and they were scared of dying in such circumstances. Similar evidence was reported by Wallace et al, 2020,families that were unable to grieve in accordance with traditional funeral practices or being unable to attend a loved one's burial undergo feeling of grief and sorrow [14] Our study found that the pandemic has caused signi cant nancial disruption among the community members. It was identi ed that many families were struggling hard in present time due to nancial insecurities including unemployment, and salary deduction.…”
Section: Discussionsupporting
confidence: 90%
“…For example, we worry as mothers our children will get sick. This is all compiled with dealing with our uncertain future, which can be considered anticipatory grief, in which we are anticipating future losses such as time spent with family, creating a normal childhood for our children, the ability to travel and engage in summer enrichment, and living in a world that is relatively safe, among others (Wallace, Wladkowski, Gibson, & White, 2020).…”
Section: Mental Healthmentioning
confidence: 99%
“…During the covid-19 pandemic grief may be significantly affected by other losses due to social distancing restrictions, such as not being with a loved one as they are dying, not being able to attend a funeral, and not being able to seek comfort in the arms of wider friends and family while grieving 29. Additional risk factors for poor bereavement outcomes and complicated grief in covid-19 include severe breathlessness, patient isolation, and disruption to the relative’s social support networks 30. Ways to mitigate these include:…”
Section: Grief and Bereavementmentioning
confidence: 99%